دور نظام البوت في تمويل مشروعات البنى التحتية بمحلية الدويم - د. عبد الله محمود عبد المجيد; مبارك إسحق محمد يوسف (White Nile Journal for Studies and Research, 2016)
This study examined the feasibility of implementing Build, Operate, and Transfer Delivery system in White Nile State, (Edduiem Locality), in addition the study identifies appropriate types of Construction projects, which could be possible implemented through BOT system. The content and literature analysis was employed to study the feasibility of BOT in Eddujem, the study looks at issues that have positive impact on the adopting of BOT. The study showsseveral results; the most important of them are that acceptance that there is great expectant for application of BOT in Edduiem locality, and for successfully and the most important